Évolution des systèmes de reproduction chez les plantes face aux changements globaux - Cheptou, Pierre-Olivier (Comptes Rendus Biologies)
Beyond species extinction, it is likely that global change modifies selection regimes in natural populations. Whereas the classical Darwinian paradigm considers evolution as a slow process, it is now accepted that populations can evolve rapidly, in a few dozen generations. Plant-pollinator relationship is a central relationship in terrestrial ecosystems and the current pollinator decline can potentially disrupt this relationship. In this paper, we explore the possibility that reproductive systems in plants evolve in the face of pollinator decline. Using the case of a recent resurrection ecology study in Viola arvensis, the field pansy, we show that the evolution of a self-fertilization syndrome, and thus the breakdown of the plant-pollinator interaction, is in progress. Beyond the species itself, the evolution of reproductive regimes in plants involves relationships between species (pollinators and higher trophic levels). Thus, this example illustrates that global change is likely to affect biodiversity at different scales: from populations (Darwinian evolution) to ecosystem functions (relationships between species). This study shows that evolutionary processes modify the functioning of ecological systems and, where applicable, the related ecosystem services.